2018
DOI: 10.1111/ppl.12801
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair in plant mitochondria – a complete base excision repair pathway in potato tuber mitochondria

Abstract: Mitochondria are one of the major sites of reactive oxygen species (ROS) production in the plant cell. ROS can damage DNA, and this damage is in many organisms mainly repaired by the base excision repair (BER) pathway. We know very little about DNA repair in plants especially in the mitochondria. Combining proteomics, bioinformatics, western blot and enzyme assays, we here demonstrate that the complete BER pathway is found in mitochondria isolated from potato (Solanum tuberosum) tubers. The enzyme activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 78 publications
(85 reference statements)
0
22
0
Order By: Relevance
“…In mitochondria of potato (Solanum tuberosum L.) tubers under hypoxia conditions, the activities of apurinic/apyrimidinic endonuclease and uracil DNA glycosylase (the enzymes of BER) were significantly increased. However, under optimal assay conditions, the mechanism of DNA repair in mitochondria in potato tuber was not so efficient as in mouse liver (Ferrando et al 2019). It can be assumed that the accumulation of DNA mutation is not the main cause of ageing in plants as very old bristlecone pine trees produce seeds with undiminished vitality, which germinate as well as seeds from younger trees (Lanner and Connor 2001).…”
mentioning
confidence: 99%
“…In mitochondria of potato (Solanum tuberosum L.) tubers under hypoxia conditions, the activities of apurinic/apyrimidinic endonuclease and uracil DNA glycosylase (the enzymes of BER) were significantly increased. However, under optimal assay conditions, the mechanism of DNA repair in mitochondria in potato tuber was not so efficient as in mouse liver (Ferrando et al 2019). It can be assumed that the accumulation of DNA mutation is not the main cause of ageing in plants as very old bristlecone pine trees produce seeds with undiminished vitality, which germinate as well as seeds from younger trees (Lanner and Connor 2001).…”
mentioning
confidence: 99%
“…Although the complete genome of A. angustifolia has not been sequenced, proteomic (dos Santos et al ) and transcriptomic (Elbl et al ) analyses identified more than 200 matches for DNA repair enzymes of all types including DNA glycosylases, AP endonuclease and DNA polymerases. We found activities corresponding to the first two steps of the BER pathway in Araucaria mitochondria, so it is likely that the whole BER pathway is present as it is in potato mitochondria (Ferrando et al ). The BER pathway is important for the cell to overcome stress conditions (Balestrazzi et al , Chen et al ).…”
Section: Discussionmentioning
confidence: 89%
“…Reports on DNA repair activity in extracts of angiosperms are rare, while they appear to be non‐existent for gymnosperms (Kimura et al , Balestrazzi et al , Joldybayeva et al ). A couple of DNA repair enzymes have been identified in mitochondria (Boesch et al ) and chloroplasts (Gutman and Niyogi ) and a recent study showed that the whole BER pathway is present in potato tuber mitochondria (Ferrando et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The product of a reaction catalyzed by DNA glycosylases AtFPG and AtOGG1 may serve as a substrate for polynucleotide 3'-phosphatase AtZDP (polynucleotide 3'-phosphatase ZDP) and AtARP (DNA-(apurinic or apyrimidinic site) endonuclease) which is the major source of AP endonuclease activity in Arabidopsis cell extracts [120,121]. Extremely low activity of OGG1 detected in potato mitochondria was also presented [122]. However, it should be treated with caution.…”
Section: Base Excision Repairmentioning
confidence: 99%